2006
DOI: 10.1637/7502-010906r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification, and Comparison of Four Isolates of Avian Paramyxovirus Serotype 2 in China

Abstract: Four Yucaipa-like viruses of avian paramyxovirus serotype 2 (APMV-2) were isolated in China from the imported Gouldian Finch (Chloebia gouldiae) and broilers in 1998-2002, and were named F4, F6, F8, and NK, respectively. Examined under electron microscope, the isolates were found to be round in shape and varying in size. The results of the hemagglutination inhibition test and indirect enzyme-linked immunosorbent assay (using monoclonal antibodies) showed some differences between the isolates and the reference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
3
23
0
Order By: Relevance
“…These results are in accordance with data in the literature showing particles with similar morphology in pigeons (Gough & Alexander, 1983), owls (Catroxo et al, 2010), ducks (Chang et al, 2001) and Gouldian Finch (Zhang et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with data in the literature showing particles with similar morphology in pigeons (Gough & Alexander, 1983), owls (Catroxo et al, 2010), ducks (Chang et al, 2001) and Gouldian Finch (Zhang et al, 2006).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, little is known about the potential pathogenic of APMV-2 to APMV-10 serotypes in captive or wild birds (Bankowski et al, 1968;Alexander et al, 1982;Zhang et al, 2006;Miller et al).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that in passerines and psittacines, the serotype 2 (APMV-2) frequently occurs triggering mild respiratory disease or high limiting, severe pneumonia, and diarrhea in passerines (Ritchie & Carter, 1995;Zhang et al) and weakness, weight loss, pneumonia, tracheitis, diarrhea with high mortality in psittacines (Collins et al, 1975, Ritchie).…”
Section: Introductionmentioning
confidence: 99%
“…Since then many APMV-2 strains have been isolated from chickens, turkeys and feral birds across the globe (Alexander et al, 1982;Asahara et al, 1973;Collings et al, 1975;Fleury et al, 1979;Goodman et al, 1988;Lang et al, 1975;Lipkind et al, 1979;Lipkind et al, 1982;Mbugua et al, 1985;Nymadawa et al, 1977;Shihmanter et al, 1997;Weisman et al, 1984;Zhang et al, 2006;Zhang et al, 2007). Serological survey of chickens and turkeys has shown a wide prevalence of APMV-2 in the United States.…”
Section: Introductionmentioning
confidence: 99%